Factors associated with elevated blood pressure or hypertension in Afro-Caribbean youth: a cross-sectional study - Ferguson, Trevor S.; Younger-Coleman, Novie O.M.; Tulloch-Reid, Marshall K.; Bennett, Nadia R.; Rousseau, Amanda E.; Knight-Madden, Jennifer M.; Samms-Vaughan, Maureen E.; Ashley, Deanna E.; Wilks, Rainford J. (PeerJ, 2018)
Background Although several studies have identified risk factors for high blood pressure (BP), data from Afro-Caribbean populations are limited. Additionally, less is known about how putative risk factors operate in young adults and how social factors influence the risk of high BP. In this study, we estimated the relative risk for elevated BP or hypertension (EBP/HTN), defined as BP ≥ 120/80 mmHg, among young adults with putative cardiovascular disease (CVD) risk factors in Jamaica and evaluated whether relative risks differed by sex. Methods Data from 898 young adults, 18–20 years old, were analysed. BP was measured with a mercury sphygmomanometer after participants had been seated for 5 min. Anthropometric measurements were obtained, and glucose, lipids and insulin measured from a fasting venous blood sample. Data on socioeconomic status (SES) were obtained via questionnaire. CVD risk factor status was defined using standard cut-points or the upper quintile of the distribution where the numbers meeting standard cut-points were small. Relative risks were estimated using odds ratios (OR) from logistic regression models. Results Prevalence of EBP/HTN was 30% among males and 13% among females (p < 0.001 for sex difference). There was evidence for sex interaction in the relationship between EBP/HTN and some of risk factors (obesity and household possessions), therefore we report sex-specific analyses. In multivariable logistic regression models, factors independently associated with EBP/HTN among men were obesity (OR 8.48, 95% CI [2.64–27.2], p < 0.001), and high glucose (OR 2.01, CI [1.20–3.37], p = 0.008), while high HOMA-IR did not achieve statistical significance (OR 2.08, CI [0.94–4.58], p = 0.069). In similar models for women, high triglycerides (OR 1.98, CI [1.03–3.81], p = 0.040) and high HOMA-IR (OR 2.07, CI [1.03–4.12], p = 0.039) were positively associated with EBP/HTN. Lower SES was also associated with higher odds for EBP/HTN (OR 4.63, CI [1.31–16.4], p = 0.017, for moderate vs. high household possessions; OR 2.61, CI [0.70–9.77], p = 0.154 for low vs. high household possessions). Alcohol consumption was associated with lower odds of EBP/HTN among females only; OR 0.41 (CI [0.18–0.90], p = 0.026) for drinking <1 time per week vs. never drinkers, and OR 0.28 (CI [0.11–0.76], p = 0.012) for drinking ≥3 times per week vs. never drinkers. Physical activity was inversely associated with EBP/HTN in both males and females. Conclusion Factors associated with EBP/HTN among Jamaican young adults include obesity, high glucose, high triglycerides and high HOMA-IR, with some significant differences by sex. Among women lower SES was positively associated with EBP/HTN, while moderate alcohol consumption was associated lower odds of EBP/HTN.
Keywords: Elevated blood pressure; Hypertension; Cardiovascular disease risk factors; Young adults; Caribbean; Blacks; Jamaica; Socioeconomic status; Prehypertension